From the parents’ perspective: a user-satisfaction survey of immunization services in Guatemala - Barrera, Lissette (BioMed Central, 2014)
BACKGROUND: Immunization coverage levels in Guatemala have increased over the last two decades, but national targets of ≥95% have yet to be reached. To determine factors related to undervaccination, Guatemala’s National Immunization Program conducted a user-satisfaction survey of parents and guardians of children aged 0–5 years. Variables evaluated included parental immunization attitudes, preferences, and practices; the impact of immunization campaigns and marketing strategies; and factors inhibiting immunization. METHODS: Based on administrative coverage levels and socio-demographic indicators in Guatemala’s 22 geographical departments, five were designated as low-coverage and five as high-coverage areas. Overall, 1194 parents and guardians of children aged 0–5 years were interviewed in these 10 departments. We compared indicators between low- and high-coverage areas and identified risk factors associated with undervaccination. RESULTS: Of the 1593 children studied, 29 (1.8%) were determined to be unvaccinated, 458 (28.8%) undervaccinated, and 1106 (69.4%) fully vaccinated. In low-coverage areas, children of less educated (no education: RR = 1.49, p = 0.01; primary or less: 1.39, p = 0.009), older (aged >39 years: RR =1.31, p = 0.05), and single (RR = 1.32, p = 0.03) parents were more likely to have incomplete vaccination schedules. Similarly, factors associated with undervaccination in high-coverage areas included the caregiver’s lack of education (none: RR = 1.72, p = 0.0007; primary or less: RR = 1.30, p = 0.05) and single marital status (RR = 1.36, p = 0.03), as well as the child’s birth order (second: RR = 1.68, p = 0.003). Although users generally approved of immunization services, problems in service quality were identified. According to participants, topics such as the risk of adverse events (47.4%) and next vaccination appointments (32.3%) were inconsistently communicated to parents. Additionally, 179 (15.0%) participants reported the inability to vaccinate their child on at least one occasion. Compared to high-coverage areas, participants in low-coverage areas reported poorer service, longer wait times, and greater distances to health centers. In high-coverage areas, participants reported less knowledge about the availability of services. CONCLUSIONS: Generally, immunization barriers in Guatemala are related to problems in accessing and attaining high-quality immunization services rather than to a population that does not adequately value vaccination. We provide recommendations to aid the country in maintaining its achievements and addressing new challenges.